Utilization of Mesenchymal Stem Cells in Kidney Transplantation: From Bench to Bedside (Iranian Journal of Kidney Diseases, 2019)
There has been ample of preclinical and animal studies whichshowed efficacy and safety of using mesenchymal stem cells (MSCs)after transplantation for tissue repair, immunosuppression ortolerance induction. However, there has been a significant progressrecently using MSCs in small clinical trials after transplantation. Recent results using MSCs after transplantation seem to befeasible and safe. However, there are some limitations to show theeffectiveness of these cells including source, dose, timing and routeof infusions. Currently, live donor kidney transplantation has beenespecially considered and development of recent regimes includingimmunosuppression drugs and MSCs administration to kidney andother organs and deceased donor transplantation would be crucial.Therefore, in this review we focused on immunomodulatory effectsof MSCs that have been extensively studied to suppress variousinflammatory responses in kidney transplantation.